Estimasi Serapan Karbon Mangrove Melalui Proses Fotosintesis di Taman Nasional Berbak-Sembilang - Tengku Zia Ulqodry; Apri Suganda; Andi Agussalim; Riris Aryawati; Afan Absori (Pusat Riset Kelautan, 2020)
Mangrove is the largest ecosystem in Berbak-Sembilang National Park (BSNP) South Sumatra. Mangrove has capability to absorb carbon dioxide through photosynthesis then store it in biomass, that known as Carbon sink. The purpose of this research was to estimate the ability of carbon fixation through the photosynthesis mechanism in the mangrove area of BSNP South Sumatra. This study was conducted in July-August 2017, at 12 observation stations. Data of carbon fixation through photosynthesis was estimated by using Leaf Area Index (LAI) method. The estimation of carbon fixation by photosynthesis was done for 17 dominan mangrove species in BNSP South Sumatera. The average amount of carbon absorbed by mangrove vegetation through photosynthesis mechanism in BNSP South Sumatera was 204.91 kg/ha/day. Avicennia marina and Rhizophora apiculata were the mangrove community that showed highest capability to absorb carbon through photosynthesis around 553.43 kg C/ha/day and 401.99 kg-C/ha/day, respectively. Individually, B. cylindrica had the highest capability of carbon fixation by photosynthesis mechanism (10.95 kg-C/ha/day). Our research recommended three mangrove species (A. marina, R. apiculata and B. cylindrica) for restoration species to increase carbon sink in BNSP South Sumatera based on their photosinthesis performances.